Metabolic dysregulation in Huntington's disease: Neuronal and glial perspectives - Ching-Pang Chang; Ching-Wen Wu; Yijuang Chern (Neurobiology of Disease)
Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder caused by a mutant huntingtin protein with an abnormal CAG/polyQ expansion in the N-terminus of HTT exon 1. HD is characterized by progressive neurodegeneration and metabolic abnormalities, particularly in the brain, which accounts for approximately 20 % of the body's resting metabolic rate. Dysregulation of energy homeostasis in HD includes impaired glucose transporters, abnormal functions of glycolytic enzymes, changes in tricarboxylic acid (TCA) cycle activity and enzyme expression in the basal ganglia and cortical regions of both HD mouse models and HD patients. However, current understanding of brain cell behavior during energy dysregulation and its impact on neuron–glia crosstalk in HD remains limited. This review provides a comprehensive summary of the current understanding of the differences in glucose metabolism between neurons and glial cells in HD and how these differences contribute to disease development compared with normal conditions. We also discuss the potential impact of metabolic shifts on neuron–glia communication in HD. A deeper understanding of these metabolic alterations may reveal potential therapeutic targets for future drug development.